Identification of Natural Food in the Digestive Tract of 1-3 Cm Kotes (Channa gachua) Seeds in Some Ponds in Malang Area - Tri Adwin Harijadi (Contributions of Central Research Institute for Agriculture, 2021)
The purpose of this study was to identify the type of food present in the digestive tract of 1-3 cm Kotes fry found at the test site. The test parameters used in this study included calculating the total length and weight of the fish, calculating the width of the fish's mouth opening, measuring the length and weight of the digestive tract of fish, observing the amount and type of food in the digestive tract, observing plankton in the waters of the study site, collecting and identification of the benthic from the study site, observation of temperature, pH and dissolved oxygen as well as data analysis which includes the method of occurrence frequency and the ratio of the length of the digestive tract to the total length of the fish. Types of food found in the digestive tract of Kotes fry measuring 1-3 cm include Navicula sp, Scenedesmus sp, Branchionus sp, Cyclops sp, Daphnia sp, Aedes sp larvae, Chironomous sp larvae. The results of the frequency of occurrence showed that the most dominant food was Chironomous sp Larvae with a value of 68.03 ± 8.68%. Judging from the ratio of the length of the digestive tract to the body length of the Kotes fry, a value of 0.52 ± 0.015 was obtained. This value indicates that the Kotes fish fry measuring 1-3 cm are classified as carnivorous fish. The results of observations of water quality at the test site were for temperatures ranging from 18.75 ± 1.160C-30.37 ± 1.060C, a pH value of 6 and a dissolved oxygen value between 1.86 ± 0.43-6.56 ± 1.01 mg/litre.